Analisis Kebutuhan Pelatihan Manajemen Persuratan Bagi Tenaga Administrasi - Ari Wibowo Sembiring; Khoirunnisa Khoirunnisa; Laila Ali Tanjung; T. Darmansha (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research examines the need for correspondence management training for administrative staff through a literature review from various related literature sources. Correspondence management is an important activity in office administration, but often does not receive adequate attention. This can cause problems such as mail flow jams, loss of important documents, and slow administration processes. To overcome this problem, appropriate training is needed for administrative staff so that they can manage correspondence effectively and efficiently. Through searching various journals, books and other literary sources, information was obtained about the importance of correspondence management, the obstacles faced by administrative staff, as well as best practices in managing correspondence. From the literature review, relevant training needs for administrative staff were identified, such as digital archiving, handling confidential letters, and the use of information technology-based correspondence management information systems. The results of this literature research provide a comprehensive picture of the needs for correspondence management training for administrative staff. These findings are the basis for designing training programs that suit the real needs of administrative staff, so that they can optimize correspondence management and support the smooth running of administrative processes in the organization.